The Study of Total IgE Reference Range in Healthy Adults in Tehran, Iran - R Shokouhi Shoormasti; Z Pourpak; MR Eshraghian; MT Haghi Ashtiani; M Jamali; M Ziedi; F Asgari Pour; M Moin (Tehran University of Medical Sciences, 2010)
Background: IgE is an antibody class that regarded as an important factor in the pathogenesis of allergic diseases, asthma, immune responses to parasitic infection and it could be responsible for the late- phase allergic response. The objective of this study was to evaluate total IgE in healthy Iranian adults, establishment of reference range of total IgE and assess helpfulness of this value in clinical diagnosis atopic and allergic diseases. Method: Three hundred sixty six healthy adults from blood transfusion volunteers (18 to 60 years) were selected in this study. A specific questionnaire (including demographic factors, smoking status and ...) was filled out for each person. Also, we evaluated effect of race and education on total IgE. These adults had no history of allergic disease. The total serum IgE level using a commercial enzyme immunoassay and CBC (Eosinophil count) was determined in them. Results: Mean of age was 37.32± 10.93 yrs and 219 cases were males and 147 females. The geometric mean of total IgE was 20.84 IU/ml (2-373 IU/ml) (95% percentile= 250) (95% confidence interval=46.27-62.70). No differences was observed between mean of IgE log in males and females (P= NS) but mean of total IgE log in females is more than males. Conclusion: Normal range of serum total IgE obtained in this study could be helpful for diagnosis of IgE-dependent allergic disease, as reference ranges in Iranian healthy adults.